Contexts of HIV-Related Risk Behaviors among Male Customers at Asian Massage Parlors in San Francisco. (4th March 2014) - Nemoto, Tooru; Iwamoto, Mariko; Eilkhani, Elnaz; Sakata, Maria; Le, Mai Nhung; Morris, Anne
Abstract : Based on focus groups for male customers who frequented Asian massage parlors in San Francisco, the present study described their sexual and drug use behaviors and attitudes toward practicing safe sex with Asian masseuses. A pervasive view among patrons was that they could engage in sex with masseuses without using a condom if they offered extra money. Their sexual behaviors with Asian masseuses were influenced by perceptions about vulnerability toward HIV/STIs, substance use behaviors, and masseuses' initiation of condom use, which was often governed by unspoken rules at parlors. Customers perceived massage parlors as being a safe place compared with street sex venues. Some customers sought emotional attachment with Asian masseuses and expressed stereotypical views toward them as being docile and submissive. Culturally appropriate HIV/STI prevention programs (e.g., communication about and practicing 100% condom use) are needed to target both customers and Asian masseuses at multiple levels (individual, owner/manager, work environment, and community levels). Also, customers' and masseuses' perceptions toward relationships at massage parlors and power dynamics need further investigation to promote safe work environments and 100% condom use at massage parlors.